(untitled) (Journal of Hama University, 2024)
The study aimed to identify common linguistic mistakes in the writings of students of the College of Education at the University of Hama, and to determine the percentage of these mistakes. The researcher follows the descriptive analytical method, using content analysis, using a card to analyze the content of linguistic mistakes and dividing them into three sections: mistakes in linguistic structure, grammatical mistakes, and spelling mistakes. The writings of a sample of students, numbering (120) male and female students, achieving a percentage of (56.60) of the original population. The results showed that grammatical mistakes came in first place among the common mistakes, and syntactic mistakes came in second place, while spelling mistakes came in first place among the common mistakes. Third, the researcher observed fourteen grammatical mistakes, twelve syntactic mistakes, and nine spelling mistakes